1999
DOI: 10.1097/00007691-199910000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic Determination of Six Antiepileptic Drugs and Two Metabolites in Microsamples of Human Plasma

Abstract: A simple, rapid, sensitive, and reproducible high-performance liquid chromatographic (HPLC) method for simultaneous determination of the antiepileptic drugs (ethosuximide, primidone, lamotrigine, phenobarbital, phenytoin, and carbamazepine) and two metabolites (carbamazepine-diol and carbamazepine-epoxide) in human plasma is described. The procedure involves extraction of the drugs from human plasma (100 microL) with ether using 9-hydroxymethyl-10-carbamyl acridan as an internal standard. The extract was evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 8 publications
1
35
0
1
Order By: Relevance
“…Over the last years, a number of validated methods for PHT measurement have been reported, usually requiring a large amount of plasma sample [6,[10][11][12][13]. In pediatric patients the available amount of sample …”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, a number of validated methods for PHT measurement have been reported, usually requiring a large amount of plasma sample [6,[10][11][12][13]. In pediatric patients the available amount of sample …”
Section: Introductionmentioning
confidence: 99%
“…The peak areas were integrated automatically by computer using a Shimadzu Class VP V 6.14 software program. The experiments were carried out on a reversed phase Phenomenex (Torrance, USA) Synergi MAX-RP C 12 analytical column (150 x 4.6mm I.D., with a particle size of 4 µm and pore size of 80 Å) maintained at 35 ºC. The LC system was operated isocratically using a mobile phase of water:acetonitrile:methanol (58.8:15.2:26, v/v/v).…”
Section: Apparatus and Chromatographic Conditionsmentioning
confidence: 99%
“…[6][7][8][9][11][12][13][14][15][16][17][18][19][20][21][22] A chiral LC method was developed and validated for the determination of phenobarbital and methylphenobarbital enantiomers in human plasma using a C 18 precolumn and a chiral column for the enantiomeric separation. 23 The RP-LC methods were developed with UV detection and using stir bar-sorptive extraction, 11 liquid-liquid extraction (LLE), 12,13,21 direct injection of plasma with manual column-switching technique, 17 SPE, 22 or protein precipitation. [18][19][20] However, some of these methods show disadvantages such as low sensitivity, complicated and extensive sample preparation, and most of them did not demonstrate any applicability for pharmacokinetic or bioequivalence studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several HPLC methods have been developed for the determination of LTG in biological fluids [118][119][120][121][122]. Shihabi et al [123] reported a CZE method for the determination of LTG in human serum.…”
Section: Lamotriginementioning
confidence: 99%